Effect of different types of immunosuppressive therapy on the parameters of TNF receptor expression in patients with rheumatoid arthritis - A. A. Alshevskaya; J. V. Zhukova; J. A. Lopatnikova; F. D. Kireev; N. S. Shkaruba; O. A. Chumasova; J. A. Shevchenko; N. A. Ilina; A. E. Sizikov; S. V. Sennikov (Acta Biomedica Scientifica, 2022)
Background. The balance of TNF receptor expression on immune cells is a key factor determining cytokine-induced activation of proapoptotic or proliferative signaling pathways. As a result, the changes in cytokine level and in expression of its receptors may be one of the mechanisms that regulate the level of systemic and local inflammation in rheumatoid arthritis (RA) and determine the degree of therapy effectiveness.   The aim. To study the effect of rheumatoid arthritis therapy on the change in the patterns of TNF receptors expression in terms of co-expression and the number of receptors on the main subpopulations of immunocompetent cells.Materials and methods. A comparative analysis of the profiles of TNF receptors type 1 and 2 (TNFR1/2) co-expression was carried out in patients with RA (n = 16) before and after having inpatient effective therapy and in comparison with a group of healthy individuals (n = 21). We compared the number of receptors and the proportion of cells expressing the corresponding receptor using flow cytometry and studied the subpopulations of regulatory T cells, T cells, B cells, and monocytes.   Results. In patients with RA, there is a significant redistribution of TNFR1 and TNFR2 expression on immunocompetent cells, while the intensity of changes is associated not only with disease severity indicators, but also with the therapy received. The key adaptive mechanism of the TNF system in long-term treatment refractory course of RA is a change in the proportion of double-positive TNFR1+TNFR2+ cells, while the effectiveness of therapy and clinical indicators of the disease severity are associated with individual variability in the parameters of type 2 receptors expression.   Conclusions. The data obtained confirm the existence of a relationship between an imbalance in the expression of type 1 and type 2 TNF receptors on immunocompetent cells and the effectiveness of response to therapy. The identified patterns of typical changes in TNFR1/2 co-expression in RA can be used as potential therapeutic targets and predictive factors for the effectiveness of therapy.